1987
DOI: 10.1148/radiology.162.1.3786768
|View full text |Cite
|
Sign up to set email alerts
|

Developmental features of the neonatal brain: MR imaging. Part II. Ventricular size and extracerebral space.

Abstract: Magnetic resonance (MR) imaging with a 0.6-T magnet was performed on 51 neonates, aged 29-42 weeks postconception. In 45 neonates, the ventricular/brain ratio (V/B) at the level of the frontal horns and midbody of the lateral ventricles ranged from 0.26 to 0.34. In six other infants a V/B of 0.36 or greater was associated with either cerebral atrophy or obstructive hydrocephalus. The width of the extracerebral space measured along specified points varied little in the neonatal period and ranged from 0 to 4 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…17 A composite adverse finding on early CUS was defined as presence of grade III or IV ICH 18 or cystic periventricular leukomalacia (cPVL) on either or both sides. A composite adverse finding on late CUS was defined as cPVL, or porencephalic cyst, or moderate-to-severe ventricular enlargement (VE, with moderate and severe VE defined as ventricular-to-brain ratio of 1:3 to 2:3 and .2:3, respectively) 19,20 on either or both sides, or shunt. For all CUS, interobserver reliability between central readers demonstrated k = 0.75 for early CUS adverse finding, and k = 0.88 for late CUS adverse finding.…”
Section: Cranial Ultrasoundmentioning
confidence: 99%
“…17 A composite adverse finding on early CUS was defined as presence of grade III or IV ICH 18 or cystic periventricular leukomalacia (cPVL) on either or both sides. A composite adverse finding on late CUS was defined as cPVL, or porencephalic cyst, or moderate-to-severe ventricular enlargement (VE, with moderate and severe VE defined as ventricular-to-brain ratio of 1:3 to 2:3 and .2:3, respectively) 19,20 on either or both sides, or shunt. For all CUS, interobserver reliability between central readers demonstrated k = 0.75 for early CUS adverse finding, and k = 0.88 for late CUS adverse finding.…”
Section: Cranial Ultrasoundmentioning
confidence: 99%
“…SAS measurements varies according to the method used in the studies [11]. In studies on healthy children, SAS was found as 1.9-5.7 mm [4,5,14].…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid space (SAS) can be assessed by various imaging modalities, including computed tomography (CT), magnetic resonance imaging and ultrasonography (US) [5,6,8,9,[11][12][13]. US is the method of choice and most commonly used modality [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is often challenging for the reporting radiologist to define the limit between normal and enlarged subarachnoid spaces. However, a cranio-cortical width of more than 10mm is generally considered pathological [31,32]. Most believe that this condition is a result of immature arachnoid villi that are unable to keep up with the rate of CSF production [33].…”
Section: Ventriculomegaly: Is It Benign External Hydrocephalus Ex-vamentioning
confidence: 99%